(untitled) (Physical Education, Health and Social Sciences, 2025)
Objectives: To compare the efficacy of combination therapy and mono therapy in improving triglycerides and low density lipoprotein cholesterol in patients uncontrolled on mono therapy. Study design: Randomized controlled trial Place and Duration of study: Department of cardiology, PAEC General Hospital, Islamabad, from 1st of December 2023 to 29th of February 2024 over a period of 3 months. Methods: A total of 142 patients taking statin monotherapy and reported with uncontrolled levels of triglycerides and LDL Cholesterol were enrolled in this study and divided in to 2 equal groups. In combination therapy group, patients were added fenofibrate (200mg once daily) to their existing treatment while in monotherapy group patients were continued with their existing statin treatment. The primary outcome was set as the change in the levels of triglycerides and LDL Cholesterol from the baseline after 2 months study period. The secondary outcome was the number of patients achieving the treatment goals at completion of study. Results: The Mean±SD of age in this study was 55.90±8.10 years. The results of primary outcomes of the study show statistically significant difference in triglycerides levels in combination group compared to monotherapy group (233.4±36.74 Vs 260.50±37.39, respectively, p=0.00), however, no statistically significant difference was present in the levels of LDL Cholesterol between the 2 groups (161.73±10.27 Vs 163.5±5.3 respectively, p=0.19). There was significant difference in the levels of total cholesterol, HDL cholesterol and the number of patients achieving their targeted levels of both these parameters in combination therapy group compared to monotherapy group (5.63% Vs 0%, respectively, p=0.04). Conclusion: Combination therapy in patients uncontrolled on mono therapy significantly improves the triglycerides levels, total cholesterol and HDL cholesterol levels. However there is no significant improvement in the LDL cholesterol levels.